Study of hyper bilirubinemia in Low Birth Weight (LBW) and Normal Birth Weight (NBW) babies - DR.V V V N S Ravi Sankar; Dr. Notu Linga Reddy; Dr. Bhimireddy Vijayalakshmi; Dr. Nalluru Lakshmi Sravanthi (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Neonatal hyper bilirubinemia implies significant jaundice usually above 15mg/dl or requiring treatment. About 60-70% of all term newborns develop some degree of jaundice while in LBW babies it goes upto 80%. Jaundice is more prevalent, severe and protracted in low birth weight babies, with more chance of producing neurological injury at lower levels of bilirubin. Methodology: This study is an attempt to compare the etiology and response to treatment modalities of hyperbilirubinemia in low birth weight and normal birth weight babies. About 150 babies including 50 low birth weight and 100 normal birth weight babies, who were admitted in NICU for neonatal hyperbilirubinemia were selected by purposive sampling and were further analyzed. The variables used for data analysis include number of children requiring phototherapy and exchange transfusion, age at initiation of phototherapy and exchange transfusion, pre phototherapy and pre exchange serum bilirubin, duration of phototherapy and rebound hyperbilirubinemia after phototherapy and exchange transfusion. Results: The most common etiological factors among low birth weight babies were prematurity, sepsis and ABO incompatibility, among normal birth weight babies were ABO incompatibility, sepsis, Rhin compatibility. In a large proportion of cases, etiology remained idiopathic. Among low birth weight babies Phototherapy was initiated early and at a lower bilirubin level. Duration of phototherapy was more, Rebound hyperbilirubinemia was higher and requirement of exchange transfusion was more. Conclusion: Hyperbilirubinemia due to incompatibilities prevailed though sepsis contributed a significant fraction among low birth weight babies. Significant hyperbilirubinemia developed earlier and persisted longer requiring prolonged phototherapy, exchange transfusion in low birth weight babies.